Effect of Annealed Duration and Temperature on Crystallinity of Ta2O5 Thin Films - H. Darmasetiawan; Irzaman Irzaman; S. G. Sukaryo; M Hikam; N. P. Bo (Indonesian Journal of Physics, 2002)
Tantalum oxide (Ta2O5) thin films were deposited on Si(100) and Si (100)/Pt (200) substrates using the chemical solution deposition (CSD) method. X-ray diffraction (XRD) measurement was employed to characterize the films. The growth condition of Ta2O5 was carried out by spin coating at 3000 rpm for 30 seconds, and then by annealing at 900 oC for 4 hours and 15 hours. The crystallinity of thin films were investigated by XRD preferred orientation (001), (010), (100), (200) on Si (100) substrate and (001), (010), (100), (202) on Si (100)/Pt (200) substrate. Increasing the duration of annealing results in better quality of crystalline thin films and the effect of high thermal energy increases the grain size. The orthorhombic structure and crystallinity of Ta2O5 thin films on Si (100) substrates and Si (100)/Pt (200) substrates were analyzed by XRD preferred orientation (001), (010) and (100), giving lattice constants a = 3.708 Å, b = 3.716 Å, c = 4.114 Å.